THE COMMON CYTOGENETIC ABNORMALITIES IN ACUTE MYELOID LEUKEMIA PATIENTS - Shaikh, Mehwish Roshan; Haider, Ghulam; Memon, Paras; Rahool, Raja; Nouman, Maryum; Beg, Shumaila; Meher, Khalil; Zahoor, Saima; Sami, Abdus; Pavan, Bhunisha (Journal of Ayub Medical College Abbottabad, 2020)
Background: Acute myeloid leukaemia (AML) is malignant neoplasms of myeloid cells categorized by clonal expansion of hematopoietic blasts of myeloid lineage in peripheral blood and bone marrow. The aim of current study is to identify the common cytogenetic abnormalities in AML patients presenting at a tertiary care hospital of Pakistan. Methods: It was a cross-sectional study conducted at the department of Medical oncology of the Jinnah Postgraduate Medical Center, Karachi from Jun 2017- Jan 2019. The non-probability consecutive sampling technique was used to select patients. Total 92 cases of AML of age 15-55 years of either gender were included in the study. The detection of cytogenetic abnormality was done on the bone marrow biopsy. The cytogenetic abnormalities were classified into the three cytogenetic risk groups as favourable, intermediate and unfavourable. For analysis of data SPSS 23 version was used. Results: The cytogenetic abnormalities were detected in 34(37%) of the AML patients while 58 (63%) patients had normal cytogenetic. Thirty-two females (34.8%) had a normal cytogenetic (46; XX), and 15 females (16.3%) had various cytogenetic abnormalities. Twenty-six males (28.3%) had normal cytogenetic (46; XY) and 19 males (20.7%) had various cytogenetic abnormalities. Most of the patients were in intermediate risk group (67.4%), followed by favourable (17.4%) and unfavourable risk group (15.2%). The most frequent chromosomal abnormalities observed were complex cytogenetic which was detected in 5 AML patients. Conclusion: In the present study cytogenetic abnormalities were found in 37% of AML patients. Sixty-seven of the AML patients were in intermediate risk group and five patients had complex cytogenetic. Hence the cytogenetic analysis provides significant information regarding prognosis of AML patients and the cytogenetic abnormalities are less than international literature. Keywords: Cytogenetic abnormalities; Acute myeloid leukaemia; Normal cytogenetic; Complex cytogenetic